Molecular phylogeny of land snail leptopoma (gastropod: cyclophoridae) in Sabah, Malaysia - Phung, Chee Chean (2015)
Arboreal land snail genus Leptopoma has extraordinary high distribution in Sabah, Malaysia. Despite their wide distribution, taxonomy of genus Leptopoma still largely depended on traditional morphological classification. The reliability of morphology-based classification is controversial because snail's morphology is highly influence by environmental factors due to land snail's low mobility. As a contribution solving these problem, I reconstructed the phylogeny of genus Leptopoma using molecular approach. Two mitochondrial genes (COI and 16S) were obtained from Leptopoma specimens and the phylogenetic trees were revealed by performing maximum likelihood and bayesian inference analysis. Besides, shell morphometric also investigated and mapped onto phylogenetic trees to test phylogenetic signal. All the DNA sequences and specimens details were established to Barcoding of Life Data Systems (BOLD), at the same time barcode gap within Leptopoma also investigated. A total of 17 Leptopoma specimens, which representing three nominal species and one related-outgroup species were included in this study. All phylogenetic trees strongly supported the monophyly of L. sericatum and L. perlucidum from Sabah. This results congruent with their morphological classification. Among the nine shell morphometrics, presence of inner ring in aperture exhibited significant phylogenetic signal. This suggested that presence of inner ring can be the reliable diagnostic character in delimitating Leptopoma species. Based on Kimura- 2-parameter distance model, barcode gap is present within genus where intra-specific distance is below 10% while inter-specific distance is above 10%. In overall, this study has contributed 38% of all the Leptopoma records in BOLD which enable others to access and make use of in other related research. Further study which include more specimens from every distribution range in Sabah is needed to elucidate a comprehensive taxonomic status of Leptopoma